Improved single channel phase‐aware speech enhancement technique for low signal‐to‐noise ratio signal. Issue 6 (1st August 2016) - Samui, Suman; Chakrabarti, Indrajit; Ghosh, Soumya Kanti
Abstract : In the state‐of‐the‐art single channel speech enhancement techniques, the short‐time spectral amplitude is modified while the effect of the phase corruption due to the contamination of additive noise is neglected. This study introduces an improved speech enhancement algorithm based on a phase‐aware multi‐band spectral subtraction technique which estimates the spectral amplitude of the clean speech signal by considering the phase of the speech and noise signal components, and uses the estimated phase of the clean speech signal for signal reconstruction in the time domain. Experimental results show that the proposed algorithm yields better performance in terms of various objective and composite quality measures and other intelligibility assessment metrics while compared with other existing spectral subtraction methods. Using the composite objective measure quality evaluation technique, it is observed that the overall signal quality of the enhanced speech signal is improved on an average by 70% at 0 dB global input signal‐to‐noise ratio by using the proposed approach.